2003
DOI: 10.1046/j.1365-2141.2003.04664.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of RAS signalling in Chinese multiple myeloma patients: absent BRAF and rare RAS mutations, but frequent inactivation of RASSF1A by transcriptional silencing or expression of a non‐functional variant transcript

Abstract: Summary. The methylation status, mutation and expression of RASSF1A, and mutations of RAS and BRAF were studied in 52 patients with multiple myeloma (MM), one plasma cell leukaemia (PCL) patient and four MM-derived cell lines. Aberrant methylation of RASSF1A was found in nine of 32 MM patients and in one of four MM cell lines (U266), where the associated loss of transcription was reversible by demethylation treatment. RASSF1A transcription was further investigated on anti-CD138-sorted plasma cell-enriched bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
13
1
Order By: Relevance
“…The regulation of RASSF1 was confirmed by RT-PCR. The RASSF1 gene has been reported to be epigenetically regulated in many cancers, including multiple myeloma, thus demonstrating that its epigenetic regulation is an important factor in the development and maintenance of neoplasia (50,51).…”
Section: Table 6 Microarray and Reverse Transcription-pcr (Rt-pcr) Comentioning
confidence: 99%
“…The regulation of RASSF1 was confirmed by RT-PCR. The RASSF1 gene has been reported to be epigenetically regulated in many cancers, including multiple myeloma, thus demonstrating that its epigenetic regulation is an important factor in the development and maintenance of neoplasia (50,51).…”
Section: Table 6 Microarray and Reverse Transcription-pcr (Rt-pcr) Comentioning
confidence: 99%
“…Costello et al (7) reported that, on average, 600 CpG islands are targets for methylation in malignant diseases. To date, f20 cancer-related genes have been identified that are frequently silenced by methylation in MM (5,8,9). Thus, identification of unknown epigenetically inactivated cancer-related genes in MM is of tremendous importance for a better understanding of the pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that RAS mutation occurs in 420% in myeloma, 1 few cases have been demonstrated to be associated with RAS activation by functional assay such as western blotting of phosphorylated ERK. Moreover, in contrast to conventional belief that ERK activation in myeloma is often caused by gain-of-function RAS mutation or RASSF1A methylation, 1,8 our case showed activating BRAF kinase V600E mutation instead, which has been shown to occur in about 2% of myeloma cases. 9 BRAF is a serine-threonine kinase, and a component of the RAS-RAF-MEK-ERK signaling pathway, which transmits mitogenic signals from activated cell surface growth factor receptors.…”
mentioning
confidence: 39%